Determining Factors of Generation Z Halal Cosmetic Product Consumers in East Kalimantan - Darmawati; Nurul Fadhilah; Muhammad Afif Ridha (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The prospect of the halal cosmetic industry both globally and nationally has a very potential trend. In Indonesia, the halal cosmetic industry is one of the industries that contribute to the improvement of the sharia economy. Along with the development of public knowledge about organic products that are friendly to the environment and do not contain non-halal ingredients, halal cosmetic products are increasingly in demand. Ironically, the great potential of the national halal cosmetic industry has not been properly utilized by local players. This study aims to analyze the determinants of consumers of halal cosmetic products. This type of research is quantitative research. The data used are primary data, with a population of Generation Z in East Kalimantan with a probability sample technique, the number of samples is 158 respondents. Data was collected by distributing questionnaires using a Likert scale and structured online using Google Forms. Based on the results of the study, it is known that cultural, social, and personal variables do not affect purchasing decisions for halal cosmetic products, while psychology has a significant influence on purchasing decisions for halal cosmetics. This means that psychological factors determine the decision of Generation Z in purchasing halal cosmetic products in East Kalimantan.